Pneumatosis Coli Mimicking Colorectal Cancer - Teresa Jacob; Mohammad Paracha; Marta Penna; Dhili Arul; Jonathan Wilson (Case Reports in Surgery)
Pneumatosis coli (PC) is a rare condition of the gastrointestinal tract involving extraluminal gas confined within the bowel wall. We report the case of a 40-year-old gentleman presenting clinically and endoscopically with suspected colorectal cancer. In light of the patient’s red flag symptoms, and carpet of polyps seen endoscopically, surgical management by an anterior resection was performed with the patient making a successful recovery. Histological analysis of the resected specimen confirmed pneumatosis coli with no evidence of colonic neoplasia. Although PC can be an incidental finding in asymptomatic patients and considered a benign condition, it can also present as a life-threatening emergency with bowel necrosis and obstruction requiring emergency surgical intervention. Also, when PC mimics malignancy, surgical management is the most appropriate step to ensure that the diagnosis of cancer is not missed.